A RECORD OF BROWN PAPER NAUTILUS ARGONAUTA HIANS LIGHTFOOT, 1786 (FAMILY: ARGONAUTIDAE) (LAMARCK, 1809) OFF THOOTHUKUDI COAST OF GULF OF MANNAR FROM INDIA (08º 35’ 22.5" N 78º 27’ 40.9" E and 08º 31’ 91.2"N 78º 25’ 32.7"E) - T.Vaitheeswaran; N. Jayakumar; V.K.Venkataramani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The brown paper nautilus, Argonauta hians Lightfoot, 1786 was recorded for the first time from Indian waters while investigating the biodiversity of the molluscs of Gulf of Mannar during June, 2011. One specimen of the said species was collected as an incidental by-catch in the trawl catch off Thoothukudi coast of Gulf of Mannar, from India, between 08º 35’ 22.5" N 78º 27’ 40.9" E and 08º 31’ 91.2"N 78º 25’ 32.7"E at a depth of 305-310 m.